Polarization Properties of Energetic Pulsars at Meterwavelengths - Dipanjan Mitra; Rahul Basu; George I. Melikidze (The Astrophysical Journal)
Polarization behavior shows a transition in the pulsar population, where energetic sources with higher spin-down energy loss, $\dot{E}\gt 1{0}^{34}$ erg s ^−1 , often have fractional linear polarization ( L / I ) close to 100%, while below this range L / I is usually lower than 50%. The polarization behavior has been primarily studied at higher frequencies above 1 GHz, and in this work, we explore the single-pulse polarization behavior in pulsars with $\dot{E}\gt 5\,× 1{0}^{33}$ erg s ^−1 at a lower frequency range of 300–750 MHz. The polarization behavior can be divided into two categories, the first with L / I > 70% where the polarization position angle (PPA) follows a single track, and a second group with L / I < 70% and scattered PPA behavior with or without orthogonal modes. However, there are some single pulses in the first category that also have lower L / I and exhibit the presence of two polarization modes along orthogonal tracks. The radio emission in pulsars arises due to coherent curvature radiation (CCR) from charge bunches, which develops due to nonlinear instabilities in the pulsar plasma forming charge separated envelope solitons. The CCR excites orthogonally polarized X and O modes oriented perpendicular and parallel to the magnetic field line planes, which detach in the plasma and propagate independently. The O mode is 7 times stronger than the X mode but gets damped in the medium. We show that incoherent mixing of the X and O modes with different levels of damping can reproduce the observed polarization features in the energetic pulsar population.